The Image of Daniil Кharms in The Works of Aglaya Veteranyi - Аnna V. Popova (Studia Litterarum)
The essay focuses on the reception of the Russian writer Daniil Kharms in the unfinished novel Attention, the Chicken Soup Bites! Daniil Kharms in Exile by the Swiss absurdist writer Aglaja Veteranyi. The purpose of the study is to highlight the features of the portrait of Kharms in this work. The essay examines Veteranyi’s biography as well as the peculiarities of her style, making an emphasis on the most significant plotforming episodes of the novel that shed light on the place and specificity of Kharms’ image. The results of the study show that Veteranyi mixes her own biographical facts and the life of the characters of other autobiographical novels and stories with the facts of Kharms’ own biography which allows for some identification of the author with the main character. The writer shows exaggerated interest in the death of Kharms as well as in his histrionic capacities; she hyperbolizes both as well as analyzes and parodies Kharms’ works. As a result, we have a complex image that combines several personalities — the novelist herself and Kharms as an exemplary absurdist writer with the features of a trickster, revolting against the laws of logic and trying to escape death by all means, also by transforming himself into other characters or objects. The motive of death and escape from / refusal of death is common to other fictional works by Veteranyi. This testifies to her unwillingness to believe in death, both in her own and of her loved ones.